Collaborative Coaching Model on Development of Experience Management for Enhancing Science Process Skill for Early Childhood Learners (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop collaborative coaching model on development of experience management for enhancing science process skill for early childhood learners. The findings indicated that the model consists of 4 main components, namely: Principle; Objective; Implementation Process with 6 steps - 1) Appointing goal, 2) Building relation, 3) Working design, 4) Providing knowledge before supervision, 5) Collaborative coaching, 6) Evaluation; and Model Evaluation. Achievement conditions of model application, those are, examination and affirmation results of the collaborative coaching model, the evaluation of suitability, feasibility and usefulness of the model by the experts were at the highest level. The result of applying the collaborative coaching model on development of experience management for enhancing science process skill for early childhood learners revealed that the teachers have gained higher knowledge and understanding on experience management to enhance science process skill for preschool learners than before provided the developed supervision model. The supervisors have increased competency of the collaborative coaching model on development of experience management for enhancing science process skill for early childhood learners. The evaluation of the collaborative coaching model on development of experience management for enhancing science process skill for early childhood learners was at a high level.